Development of frozen buco puree (Cocos Nucifera Linn.) - Delos Reyes, Elenita E. (1978)
Frozen buco puree was developed and the product was characterized in terms of soluble solids content in degrees Brix and viscosity before and after freezing upon thawing of the puree. Results of objective and sensory evaluations revealed that it would be best to produce buco puree with a 1:1 ratio of buco meat to buco water (weight/weight) and adjusting the soluble solids content of the puree to 24° Brix. The freezing study showed that the minimum freezing time required for the buco puree packed in one half and one pint plastic containers would be 5.0 and 7.5 hours respectively. Microbiological examination and evaluation of cost of the final product were also done in this study.